Rhizoctonia mycorrhizae application and watering intervals on Dendrobium violaceoflavens seedling: a study of its effect on drought stress - R Soelistijono; Daryanti Daryanti; Haryuni Haryuni; Irvansyah Cahya Perwita; Dian Rakhmawati (Jurusan Agroteknologi, 2022)
Dendrobium violaceoflavens merupakan spesies asli Papua, habitat alaminya adalah daerah dengan curah hujan tinggi sehingga akan menjadi masalah bila dibudidayakan dan terlambat dalam penyiraman. Penelitian bertujuan mengetahui pengaruh aplikasi Rhizoctonia mikoriza dan interval penyiraman pada pertumbuhan vegetatif bibit D. violaceoflavens terhadap cekaman kekeringan (faktor abiotik). Penelitian menggunakan Rancangan Acak Lengkap (RAL) dengan 2 faktor dan 5 ulangan. Faktor pertama: dengan dan tanpa aplikasi Rhizoctonia mikoriza, faktor kedua adalah interval penyiraman 2 hari, 4 hari dan 6 hari. Hasil penelitian menunjukkan [1] aplikasi Rhizoctonia mikoriza berpengaruh nyata terhadap tinggi tanaman dengan nilai tertinggi 2,43 cm, jumlah daun 3,17 helai, dan jumlah akar 4,6 helai; [2] Interval penyiraman berpengaruh nyata terhadap tinggi tanaman dengan nilai tertinggi 2, 85 cm, jumlah daun 3,35 helai, jumlah akar 5,27 helai, dan bobot segar 1,23 g; [3] Interaksi pemberian Rhizoctonia mikoriza dan interval penyiraman 4 hari berpengaruh nyata pada panjang daun 1,90 cm dan jumlah daun 3,70 helai, dan pada akar terbentuk struktur peloton. Hasil terbaik diperoleh pada aplikasi Rhizoctonia mikoriza dan interval penyiraman 4 hari dalam penanggulangan cekaman kekeringan.ABSTRACTDendrobium violaceoflavens is a native species of Papua, its natural habitat is an area with high rainfall that will be a problem if it is cultivated and watering is delayed. The aim of this study was to determine the effect of Rhizoctonia mycorrhizae application and watering interval on vegetative growth of D. violaceoflavensseedlings on drought stress (abiotic factors).Research used a Completely Randomized Design (CRD) with 2 factors and 5 replications. First factor was with and without application of Rhizoctonia mycorrhizae, second factor was watering interval of 2 days, 4 days and 6 days. The result showed that [1] the application of Rhizoctonia mycorrhizae had a significant effect on plant height with the highest value of 2.43 cm, number of leaves 3.17 leaves, number of roots 4.6 leaves; [2] watering interval significantly affected on plant height with the highest value of 2.85 cm, number of leaves 3.35 sheets , number of roots 5.27, fresh weight of 1.23 g; [3] Interaction between Rhizoctonia mycorrhizae and watering interval of 4 days significantly affected on leaf length 1.90 cm, leaf number 3.70 sheets and a peloton structure was formed on the root. Best results were obtained on the application of Rhizoctonia mycorrhizae and watering interval of 4 days in overcoming the drought stress.